تقييم فعالية التكوين في المؤسسات الطاقوية " حالة مؤسسة سونالغاز – ورقلة" - دبون, عبد القادر; ججاج, مراد (جامعة الوادي - University of Eloued, 2016)
This study focused on evaluating the performance of training in economic energy companies: Case SONELGAZ Ouargla. The objective of our study is to highlight the role of training in improving worker skills and performance in business. To perform this study, we developed a questionnaire of twenty six (26) questions and comprises three (03) axes deal the axes of the study. The questionnaire was distributed to a random sample of thirty Cinque (35) individuals distributed in three (03) groups: controlled, delivery agents and managers. The study concluded that: - The conditions for training were favorable for successful training. - The training programs are compatible aves objectives of the training. - The training plays a fundamental role in improving behavior and organizational performance of the staff. - The training allows increasing the company's turnover. - Finally training reduced significantly workplace accidents
مقال
Keywords: تكوين، سونالغاز، فعالية، أداء، تقييم.; Training, SONELGAZ, Effective, Performance, Evaluation.